English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can someone tell me if this statement is true? 11x^2 + 7(17x -x^2) + 9x = 4x^2 +128x

2007-06-15 16:29:26 · 7 answers · asked by ambi565 2 in Science & Mathematics Mathematics

7 answers

yes it is

2007-06-15 16:32:19 · answer #1 · answered by JR 1 · 0 0

Let's see...
11x^2 + 7(17x -x^2) + 9x = 4x^2 +128x
11x^2 + 7*17x - 7x^2 + 9x = 4x^2 +128x
4x^2 + 119x + 9x = 4x^2 +128x
128x = 128x
x = x
Yes, the original statement is true.

2007-06-15 23:32:52 · answer #2 · answered by Anonymous · 0 0

11x^2 + 7(17x -x^2) + 9x = 4x^2 +128x
11x^2 + 7*17x - 7x^2 + 9x - 4x^2 -128x = 0
4x^2 + 119x + 9x - 4x^2 +128x = 0
128x - 128x = 0
0 = 0

The statement is true.

2007-06-16 00:26:56 · answer #3 · answered by Anonymous · 0 0

yes its true,

when you expand the left side

11x^2 + 7(17x -x^2) + 9x
= 11x^2 + 119x - 7x^2 + 9x
= 4x^2 + 128x

therefore since the left hand side of the eq is the same as the right hand side of the eq, the statement is true

2007-06-15 23:34:48 · answer #4 · answered by davin 2 · 0 0

11x^2+7(17x-x^2)+9x = Left Hand Side (L.H.S.)

4x^2+128x = Right Hand Side(R.H.S.)

Therefore L.H.S.= 11x^2+7*17x-7*x^2+9x

= 11x^2+119x-7x^2+9x

Combining Common Terms

= 11x^2-7x^2+119x+9x

= 4x^2+128x

= R.H.S. hence True
From Abhishek(www.eduwizards.com)

2007-06-15 23:47:06 · answer #5 · answered by Anonymous · 0 0

11x^2 + 7(17x-x^2) + 9x
= 11x^2 + 119x - 7x^2 + 9x
= 11x^2 - 7x^2 + 119x + 9x
= 4x^2 + 128x

It's a true statement.

2007-06-15 23:33:08 · answer #6 · answered by lithiumdeuteride 7 · 0 0

11x^2+7(17x-x^2)+9x
=11x^2+119x-7x^2+9x
=4x^2+128x
the statement is true.

2007-06-15 23:36:37 · answer #7 · answered by Anonymous · 0 0

fedest.com, questions and answers